Sociological Analysis of Sexual Harassment in Iran: Emphasizing the Position of Women in the Workplace - Mesri, Katayoun (Hawwa, 2025)
This study analyses the most important causes and effects of sexual harassment from the sociological perspective within the contemporary Iranian workplace. In addition to the ambiguity in the definition and exact examples of sexual harassment, another problem is that many types of offensive behavior against women in the labor market are not considered as harassment. Accurately knowing the causes of harassment will help combat this problem. Qualitative methods and grounded theory paradigm are used in this research. Data are obtained from in-depth and semi-structured interviews with thirty female victims of harassment of different ages who work in various professional positions. After studying the information and coding all the interviews, perpetrators of sexual harassment in the workplace are divided into two groups. Previously investigated reasons studied in feminist theories and those related to social structures and the historical context of Iran and similar countries have been taken into account. After grouping the data according to criteria explained here, all the categories have been collected under the central category of “patriarchy” which is based on traditions and ideology. This category is explained in the article based on the analysis model of sexual harassment in Iran.